#TITLE_ALTERNATIVE# - LESTARI (NIM 23004011), DIANIKA
Pervaporation is an alternative separation process using membrane which allows separations of organic mixtures and dehydrates organic solvents with low energy consumption. Pervaporation can also separate azeotropes, close-boiling mixtures, thermally sensitive compounds, and removes component present in low concentrations by using the difference of solubility and diffusivity of permeating components. Pervaporation process performance is determined from permeate selectivity and flux. Increase of permeate selectivity and flux means also increasing performace of pervaporation. However, increasing product flux may contribute on decreasing selectivity. According to that, optimization of membrane performance and separation condition is necessary on improving separation quality. This research is aim to study the effect of clay and zeolite incorporation as filler component in polymeric membrane and to optimize process variable (feed temperatur and filler concentration) in ethanol-water mixture pervaporation using Central Composite Design statistical method. The research consists of membrane preparation, pervaporation process, and optimization. Feed are ethanol-water mixture 8o1o-wt ethanol with temperature varying between 30-50oC and downstream pressure 0.5 mbar. Polymeric membrane cellulose acetate (CA) is used and modification will be done by depositing 10-30 %-wt CA of bentonite clay and zeolite Malang in the polymer matrix. From the obtained results, bentonite clay and natural zeolite Malang incorporation have successfully improved both CA membrane flux and selectivity. However, clay-filled CA membrane gives better performance with flux 1.80 kg/m2.h and selectivity 1701 at feed temperature 38oC and clay content 21%-wt CA (optimized result). The physicochemical properties of the clay and zeolite, primarily pore structure and size, degree of hydrophilicity, and particle size, significantly influence membrane pervaporation properties. Increase of feed temperature and filler content result in an increase of membrane flux, and in a decrease of selectivity. Interaction effects between feed temperature and clay content in clay-filled CA membrane can minimize decrease in selectivity because of increasing feed temperature.